Preparation and characterization of a copper based Indian traditional drug: tamra bhasma - Wadekar, M. P.; Rode, C. V.; Bendale, Y. N.; Patil, K. R.; Prabhune, Asmita (Journal of Pharmaceutical and Biomedical Analysis, 2005)
The copper based Indian traditional drug `tamra bhasma' is administered for various ailments since long. Its synthesis involves treating metallic copper with plant juices and then repeated calcination in presence of air so that the metallic state is transformed into the corresponding oxide form traditionally known as `bhasma'. In this work, we present a systematic characterization of this traditional drug using various techniques like X-ray diffraction (XRD), scanning electron microscopy (SEM)-energy dispersive X-ray analysis (EDX), X-ray photoelectron spectroscopy (XPS), infrared spectroscopy (IR), thermogravimetry (TG) and surface area measurement. The results obtained were found to match very well with those of a standard copper oxide confirming the composition of the drug sample. In addition, some specific findings were also made which could help in interpreting the therapeutic properties of the traditional drug `tamra bhasma'. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: copper oxide; crystallite size; tamra bhasma; traditional medicine; XPS of copper oxide; XRD

Reaction kinetics of liquid phase air oxidation of p-cresol to p-hydroxybenzaldehyde - Kshirsagar, V. S.; Nadgeri, J. M.; Tayade, P. R.; Rode, C. V. (Applied Catalysis A-General, 2008)
The kinetics of liquid phase oxidation of p-cresol to p-hydroxybenzaldehyde has been investigated using insoluble cobalt oxide (CO3O4) catalyst at oxygen partial pressures in the range 0.1-1.5 MPa, reaction temperatures 333-393 K, p-cresol concentrations 0.49-1.53 kmol/m(3) and catalyst loadings 0.38-3.03 kg/m(3). The effects of oxygen partial pressure, reaction temperature, p-cresol concentration and catalyst loading on the initial rate of reaction have been studied. The initial rate varied linearly with catalyst loading up to 1.5 kg/m(3) beyond which it was independent of the catalyst loading while first-order dependence was observed with variation in oxygen partial pressure. A rate expression has been proposed considering Langmuir-Hinshelwood (LH) type mechanism, based on the initial rate data. A batch reactor model was also developed based on the kinetics studied and the concentration time profile predicted by the model was in good agreement with the experimental data. The activation energy for the liquid phase oxidation of p-cresol was found to be 39.6 kJ/mol. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Co3O4; kinetics; p-cresol oxidation; XPS; XRD